Biofabrication of prevascularized spheroids for bone tissue engineering by fusion of microvascular fragments with osteoblasts - Wrublewsky, Selina; Schultz, Jessica; Ammo, Tekoshin; Bickelmann, Caroline; Metzger, Wolfgang; Später, Thomas; Pohlemann, Tim; Menger, Michael D.; Laschke, Matthias W. (Frontiers in Bioengineering and Biotechnology, 2024)
Spheroids are promising building blocks for scaffold-free bone tissue engineering. Their rapid vascularization is of major importance to guarantee their survival after transplantation. To achieve this, we herein introduce the biofabrication of prevascularized spheroids by fusion of adipose tissue-derived microvascular fragments (MVF) with osteoblasts (OB). For this purpose, 200 MVF from donor mice and 5,000, 10,000 or 20,000 murine OB (MC3T3-E1) were co-cultured in a liquid overlay system for 3 days to generate OB + MVF spheroids. OB mono-culture spheroids served as controls. During the generation process, the diameters of all spheroids progressively decreased, resulting in compact, viable spheroids of homogeneous sizes. MVF promoted the maturation of spheroids containing 5,000 OB, as shown by an accelerated decline of cell proliferation due to contact inhibition. Moreover, MVF most effectively reassembled into new microvascular networks within these small spheroids when compared to the other spheroid types, indicating the most beneficial MVF to OB ratio. Accordingly, these spheroids also showed a high angiogenic sprouting activity in vitro. In contrast to OB spheroids, they further rapidly vascularized in vivo after transplantation into dorsal skinfold chambers. This was caused by the interconnection of incorporated MVF with surrounding blood vessels. These findings indicate that OB + MVF spheroids may be suitable for bone tissue engineering, which should be next tested in appropriate in vivo bone defect models.